2017
DOI: 10.1075/lllt.48.05dor
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing learner characteristics in a complex, dynamic world

Abstract: The complex dynamic systems turn in second language acquisition has raised several fundamental challenges to studying learner characteristics, because a systemic perception of mental functioning that is characterized by nonlinear relations undermines the traditional theoretical basis of individual differences as distinct and stable learner attributes. This being the case, how can we account for the widely observed learner differences? Based on McAdams and Pals' (2006) personality construct, this chapter outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Building on the above findings, we summarized the critical characteristics of successful online English learners: (1) driven by integrative or instrumental motivation; (2) exhibiting an appropriate range of emotional attachment; (3) constantly reflecting on their English learning performance; (4) perceiving and understanding the value of English learning; (5) possessing an internal locus of self-evaluation and control; (6) exhibiting self-directed English learning skills towards a specific target or goal; (7) having interpersonal, collaborative and communication skills; (8) possessing good self-control of English learning anxiety, especially during tests; (9) treating the negative evaluations with peace and calm; (10) presenting self-directed learning skills during the implementation of time management and various cognitive learning strategies; (11) exhibiting enough competence in handling online learning tools and technologies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Building on the above findings, we summarized the critical characteristics of successful online English learners: (1) driven by integrative or instrumental motivation; (2) exhibiting an appropriate range of emotional attachment; (3) constantly reflecting on their English learning performance; (4) perceiving and understanding the value of English learning; (5) possessing an internal locus of self-evaluation and control; (6) exhibiting self-directed English learning skills towards a specific target or goal; (7) having interpersonal, collaborative and communication skills; (8) possessing good self-control of English learning anxiety, especially during tests; (9) treating the negative evaluations with peace and calm; (10) presenting self-directed learning skills during the implementation of time management and various cognitive learning strategies; (11) exhibiting enough competence in handling online learning tools and technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Given that self-regulation is context-specific [18], we focus on academic English writing. Three common learner characteristics, namely motivation, anxiety, and learner beliefs, have consistently been found to be consequential for foreign language learning performance [7,8]. Past studies revealed the separate roles of foreign language learning motivation, anxiety and learner beliefs in predicting learners' self-regulation [9,[11][12][13].…”
Section: The Present Study and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations